A Prospective Cohort Study of Fertility Desire, Unprotected Sex, and Detectable Viral Load in HIV-Positive Female Sex Workers in Mombasa, Kenya. (1st July 2018) - Wilson, Kate S.; Wanje, George; Masese, Linnet; Simoni, Jane M.; Shafi, Juma; Adala, Lucy; Overbaugh, Julie; Jaoko, Walter; Richardson, Barbra A.; McClelland, Raymond S.
Abstract : Background: Little is known about fertility desire in HIV-positive female sex workers. Fertility desire could increase HIV transmission risk if it was associated with condomless sex or lower adherence to antiretroviral therapy. Methods: A prospective cohort study was conducted among 255 HIV-positive female sex workers in Mombasa, Kenya. Using generalized estimating equations, fertility desire was evaluated as a risk factor for semen detection in vaginal secretions by prostate-specific antigen (PSA) test, a biomarker of condomless sex, detectable plasma viral load (VL), and HIV transmission potential, defined as visits with positive PSA and detectable VL. Results: The effect of fertility desire on PSA detection varied significantly by nonbarrier contraception use ( P -interaction < 0.01). At visits when women reported not using nonbarrier contraception, fertility desire was associated with higher risk of semen detection [82/385, 21.3% vs. 158/1007, 15.7%; adjusted relative risk (aRR) 1.58, 95% confidence interval (CI): 1.12 to 2.23]. However, when women used nonbarrier contraception, fertility desire was associated with lower risk of PSA detection (10/77, 13.0% vs. 121/536, 22.6%; aRR 0.58, 95% CI: 0.35 to 0.94). Fertility desire was not associated with detectable VL (31/219, 14.2% vs. 128/776, 16.5%; aRR 0.82, 95% CI: 0.46 to 1.45) or higher absolute risk of transmission potential (10/218, 4.6% vs. 21/769, 2.7%; adjusted risk difference = 0.011, 95% CI −0.031 to 0.050). Conclusions: Fertility desire was associated with higher risk of biological evidence of semen exposure when women were not using nonbarrier contraceptives. Low HIV transmission potential regardless of fertility desire suggests that the combination of condoms and antiretroviral therapy adherence was effective. Abstract : Supplemental Digital Content is Available in the Text.